Development of Eco-Friendly Packaging Films from Soyhull Lignocellulose: Towards Valorizing Agro-Industrial Byproducts - Sumi Regmi; Sandeep Paudel; Srinivas Janaswamy (Foods, 2024)
Due to their inability to biodegrade, petroleum-based plastics pose significant environmental challenges by disrupting aquatic, marine, and terrestrial ecosystems. Additionally, the widespread presence of microplastics and nanoplastics induces serious health risks for humans and animals. These pressing issues create an urgent need for designing and developing eco-friendly, biodegradable, renewable, and non-toxic plastic alternatives. To this end, agro-industrial byproducts such as soyhulls, which contain 29–50% lignocellulosic residue, are handy. This study extracted lignocellulosic residue from soyhulls using alkali treatment, dissolved it in ZnCl2 solution, and crosslinked it with calcium ions and glycerol to create biodegradable films. The film formulation was optimized using the Box–Behnken design, with response to tensile strength (TS), elongation at break (EB), and water vapor permeability (WVP). The optimized films were further characterized for color, light transmittance, UV-blocking capacity, water absorption, contact angle, and biodegradability. The resulting optimized film demonstrated a tensile strength of 10.4 ± 1.0 MPa, an elongation at break of 9.4 ± 1.8%, and a WVP of 3.5 ± 0.4 × 10−11 g·m−1·s−1·Pa−1. Importantly, 90% of the film degrades within 37 days at 24% soil moisture. This outcome underscores the potential of soyhull-derived films as a sustainable, innovative alternative to plastic packaging, contributing to the circular economy and generating additional income for farmers and allied industries.